Students’ perception towards modern technology as teaching Aids - Abdullah, Raja Nazim; Abdul Muait, Junaidah; Ganefri, Ganefri (Asian Journal of Assessment in Teaching and Learning, 2019)
Education is any combined of learning experiences designed to help learners with the opportunity exploration of knowledge. This paper aims to highlight the substance of considering students’ perceptions of modern approach teaching and learning process. To accomplish this objective, researchers identified 45 subjects relevant to the research objective of the recent study. The result indicates that student’s perceptions regarding teaching aids using modern technology are significant, consider modern education as a viable option to an effective education. The findings of the study provide grasp of perspective into the administration of higher learning institutions regarding the aspect that lead to the satisfaction as university students.